(untitled) (Journal of the College of Education for Women, 2022)
The study aimed to know the degree to which Islamic education teachers employ the strategy of directed discovery in teaching to develop higher thinking skills (analysis, synthesis, and evaluation) among sixth-grade students at the basic stage in East Nile Province, Khartoum State - Sudan. The researcher used the descriptive-analytical method, and adopted a questionnaire that consisted of (15) indicators representing the skills of analysis, synthesis, and evaluation as a tool of the study. A random sample of (175) Islamic education teachers was selected, from the Department of Basic Education. The data were analyzed according to the Statistical Packages for Social Sciences (SPSS) program, and the results of the study have shown that the use of the directed discovery strategy by Islamic education teachers came (with a medium degree) in the axes of the indicators of the tool (analysis, synthesis, and evaluation), as well as in its calculation of their averages concerned with the three skills. This requires much more attention to be given to the employment of the directed discovery. As such a strategy help students to develop their skills and solve the problems they face. The researcher has recommended the necessity of creating applications and programs that help Islamic education teachers to develop their teaching capabilities using new and advanced methods of teaching, in order to raise their competencies and develop their students’ higher thinking skills.